The Role of Street Vendors in Local Economic Development: Exploring Their Contribution to Regional Economy - Febry Yeni Anwar; Karno karno (Journal of Social Research, 2024)
This study aims to explore the role and contribution of Street Vendors (PKL) in local economic development. Through data collection from 50 respondents involved in PKL activities, analysis was conducted on demographic characteristics, types of products sold, and daily earnings of the vendors. The results show that the majority of respondents are within the productive age range (27-40 years), predominantly male, with educational backgrounds of SMP (junior high school) and SD (elementary school), and an average trading experience between 2 to 5 years. The most sold products are food, with 95% of respondents contributing to the local economy by paying retribution when trading in places that require an entrance fee. Validity testing of the questionnaire indicates that all questions are well-measured, while reliability testing yields values above 0.7, indicating that the research instrument is reliable. Moreover, frequency analysis shows that 60% of respondents are food traders, with an Independent Samples T-Test revealing that the average daily earnings of food vendors reach Rp 250,000, while non-food vendors average only Rp 180,000, indicating a significant difference. This research emphasizes the important role of PKL in creating jobs, increasing community income, and contributing to local economic sustainability, and is expected to provide insights for decision-making in policies that support the development of the informal sector and the improvement of community welfare.